Testing for near I(2) trends when the signal-to-noise ratio is small - Katarina Juselius (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
Researchers seldom find evidence of I(2) in exchange rates, prices, and other macroeconomics time series when they test the order of integration using univariate Dickey-Fuller tests. In contrast, when using the multivariate ML trace test they frequently find double unit roots in the data. The paper demonstrates by simulations that this often happens when the signal-to-noise ratio is small
Keywords: C1; C18; C22; C32; C52; 330; Univariate and multivariate unit root tests; double unit roots; near I(2)